Financial Management of Students with Special Needs in Increasing Guardian Trust - Krista Alifa Setyaningrum; Afiful Ikhwan; Rabiyatul Jasiyah (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
Children with special needs must be educated informally and formally to develop their intellectual skills. Before putting children with special needs into school, parents need to find the right school by looking at various aspects, one of which is related to financing and financial management. In this case, researchers conducted research at the ‘Aisyiyah Ponorogo Special School to know the school's financial management in order to be able to increase the trust of student guardians. This study used a descriptive qualitative method. Researchers obtained data using observation, interviews, and documentation. The focus of the problem in this study is financial management, financing, and the trust of student guardians at 'Aisyiyah Ponorogo Special School. Based on the data obtained, the financial management of students with special needs at ‘Aisyiyah Ponorogo Special School is carried out by making a budget plan, clear transparency of funds to student guardians, and evaluation meetings at the end of each school budget year. Sources of funds were obtained from voluntary donations from students, assistance from the Ponorogo Regency Education Office, the Smart Indonesia Program, and the 'Aisyiyah Foundation.